1989
DOI: 10.1103/physrevb.39.8772
|View full text |Cite
|
Sign up to set email alerts
|

Novel features of quantum conduction in a constriction

Abstract: The effects of the geometry and temperature on the quantum conductance for one-dimensional (1D) ballistic transport through a constriction in a 2D electron gas are investigated by use of a refined formalism. As the length of the constriction increases, weak oscillations around the classical conductance evolve into a steplike structure and the resonances on the plateaus become pronounced. Quantization at integer multiples of 2e2/h occurs only for uniform constriction of finite length. At finite temperature of 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

1990
1990
2008
2008

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(40 citation statements)
references
References 7 publications
2
38
0
Order By: Relevance
“…The total thermal conductance becomes expects that each subband in the wire having Ω i,min = 0, that formed by increasing the cross section, leads to a jump in K as in the electrical conduction. However, the amplitude of steps decreases exponentially with increasing Ω i,min at given low temperature T. Furthermore, an important difference between the electrical and thermal conductance is that all the modes of a given branch i contribute to K o , whereas the quantum ballistic electrical conduction in the 1D channels 8,25 is governed by the Fermi-Dirac distribution.…”
Section: Uniform Dielectric Wirementioning
confidence: 99%
See 1 more Smart Citation
“…The total thermal conductance becomes expects that each subband in the wire having Ω i,min = 0, that formed by increasing the cross section, leads to a jump in K as in the electrical conduction. However, the amplitude of steps decreases exponentially with increasing Ω i,min at given low temperature T. Furthermore, an important difference between the electrical and thermal conductance is that all the modes of a given branch i contribute to K o , whereas the quantum ballistic electrical conduction in the 1D channels 8,25 is governed by the Fermi-Dirac distribution.…”
Section: Uniform Dielectric Wirementioning
confidence: 99%
“…shows novel features [1][2][3][4][5][6][7][8] owing to two facts: (1) The electronic states confined in directions which are perpendicular to the one for the current flow are quantized. The level spacings 9 , ∆ǫ i = ǫ i+1 − ǫ i , of the quantized states of the nanoparticle are finite but strongly size and geometry dependent.…”
Section: Introductionmentioning
confidence: 99%
“…The different spatial extension of edge channels and magnetoelectnc subbands leads to an entirely different sensitivity to scattermg processes in weak and strong magnetic fields Firstly, the zero-field conductance quantization is destroyed by a small amount of elastic scattermg (due to impunties or roughness of the channel boundanes, cf Refs 313,316,317,407,and 408), while the QHE is robust to scattermg 97 This difference is a consequence of the suppression ofbackscattenng by a magnetic field discussed m Section 13b, which itself follows from the spatial Separation at opposite edges of edge channels moving m opposite directions Second, the spatial Separation of edge channels at the same edge in the case of a smooth confinmg Potential opens up the possibihty of adiabatic transport (i e, the füll suppression of interedge channel scattermg) In weak magnetic fields, adiabaticity is of importance within a pomt contact, but not on longer length scales (cf Sections 13 a and 15 a) In a wide 2DEG region, scattermg among the modes in weak fields estabhshes local equilibnum on a length scale given by the melastic scattermg length (which m a high-mobility GaAs-AlGaAs heterostructure is presumably not much longer than the elastic scattermg length /~10μηι) The Situation is stnkmgly different m a strong magnetic field, where the selectwe population and detection of edge channels observed by van Wees et al 426 has demonstrated the persistence of adiabaticity outside the pomt contact…”
Section: Edge Channels and The Quantum Hall Effectmentioning
confidence: 99%
“…Having the parameterized form of the potential and treating tip and sample in the free-electron approximation, ~ is obtained by evaluating the expectation value of the current operator in terms of current-carrying states, and integrating it over the Fermi sphere. The current-carrying states, in turn, are calculated by a transfer matrix method [15]. This method has a wide range of applications covering tunneling as well as ballistic transport, even including the field emission of electrons.…”
Section: Tip-sample Interaction Effectsmentioning
confidence: 99%